Partial bilateral mesencephalic lesions affect D 1 but not D 2 binding in both the striatum and cortex - Pioli, Elsa; Sohr, Reinhard; Meissner, Wassilios; Barthe, Nicole; Gross, Christian E.; Bezard, Erwan; Bioulac, Bernard H. (Neurochemistry international, 2004)
The substantia nigra pars compacta (SNc) and the ventral tegmental area (VTA) are the two major mesencephalic dopaminergic systems. Mesencephalic dopamine denervation is followed by long-term modifications in striatum and cortex that preserve dopamine functions. Here, we have studied the impact of isolated bilateral 6-hydroxydopamine lesioning of the SNc or the VTA on D 1 and D 2 dopamine receptor binding in striatal and cortical areas of rat. Neither SNc nor VTA bilateral partial lesioning changed D 2 binding at the striatal or cortical level. Intriguingly, only VTA lesioning increased D 1 binding in the cortex, whereas both bilateral partial lesioning of the SNc or the VTA increased striatal D 1 binding. This suggests that increased cortical D 1 binding could be an indicator of VTA lesioning. Further behavioural experiments may explain the pathophysiological meaning of increased cortical D 1 binding, and determine whether this observation is involved in compensatory mechanisms.